Pengaruh Personal Selling dan Display terhadap Intensi Pembelian Produk Distro di Kediri - Setiawati, Ike; Sudjiono; Nursamsu; Subianti, Tutut (Universitas Kadiri, 2023)
This study aimed to analyze the influence of personal selling and display of the product purchase intentions in steady distributions store. The research data was obtained from questionnaires (primary) of the product in store steady distributions. The findings showed that personal selling and display simultaneously (simultaneous) positive effect on purchase intentions, partial (t test) is obtained that display variable and dominant positive effect on purchase intentions. Of 29.8% variable purchase intention can be explained by the independent variable while the remaining 70.2% is explained by other variables outside of this study.